How COVID-19 Affected Burnout and Job Satisfaction Levels Among the Healthcare Workers in Jordanian Hospitals - Amer, STUDENT PhD.MHA, RN, Bani Ahmad (International Journal of Innovative Research in Medical Science, 2021)
Aim: To establish how COVID-19 affected the burnout and job satisfaction levels among the health care provider in Jordan hospitals. Methodology: The online survey questionnaire was distributed to 160 nurses, doctors, and specialists and 152 responses were captured in the Google form feedback from healthcare workers from Jordan hospitals. The survey questions wanted responses related to establishment of job satisfaction and burnout levels during the COVID-19 pandemic. The questionnaire contained questions investigating the nurses' and doctors' demographic factors, work-related variables, and personal experiences. Additionally, the provision of basic needs at the workplace were investigated, and the world Health Organization-5 well-being index was established through the questionnaires (Hamdam et al., 2020). Different statistics measurements were used. Descriptive statistics were used to summarize both the background information about the healthcare providers and burnout levels. Results: From the 152 healthcare professionals filed their responses, 32.6% were males, and the rest were females. Approximately 48%.13% and 16% were nurses, doctors, and pharmacists. Burnout was caused by exhaustion, depression, anxiety, and overtime working time. 7% of the nurses were satisfied with the work, while 72.5% were not satisfied. Approximately 24% of the male healthcare providers demonstrated resilience in employment, while 5% of the female healthcare professionals demonstrated burnout and total withdrawal due to the scourging effects of COVID-19 (Abujilban et al., 2021). The healthcare providers that received psychological support from their families seemed strong and suffered lower burnout levels. The fear of infection created anxiety that led to stress, and high burnout levels. Conclusions: COVID -19 led to increased levels of burnout and lack of job satisfaction. The hospitals in Jordan were not prepared, and the fear of nurses and doctors getting infected created more anxiety. The healthcare motivation and energy to work reduced to a bare minimum.